Diagnosis: the biopsy - Falconi, Luis M (Cirugía del Uruguay, 1973)
The pathological identification of soft tissue tumors and their correct histogenetic classification are essential prior to any treatment. either after a total resection of the lesion or through a biopsy. Incisional biopsy is the most convenient and, if necessary, can be replaced by puncture aspirational. Extemporaneous biopsy is indicated when a preoperative biopsy was not possible before.